O modo de dizer da teoria musical: uma reflexão sobre a terminologia de Schenker (Orfeu, 2021)
The translation into Portuguese of some terms of Heinrich Schenker’s music theory is discussed. Focusing mainly on the terms Urlinie and Ursatz, we seek to conduct a debate about the meaning of such concepts, meaning that appears as the strictly musical manifestation of the principle of unity of the work of art. Such a principle assumes an emblematic role in Schenker’s theory through the concept of organic coherence and thus the concept of organism. The argument focuses on the multiple meanings of the word Satz, highlighting its uses in the musical vocabulary and, especially, in Schenker’s writings, more specifically, as a forming element of the term Ursatz. The discussion provides an opportunity for reflection on the terms proposed by Schenker and their implications and scope when translated into other languages, times, and places.
Keywords: Austro-Germanic music theory; music and philosophy; Heinrich Schenker; organic coherence